Pemanfaatan Macromedia Flash 8.0 Sebagai Sarana Belajar Dalam Pengenalan Nabi Dan Rasul - Agustin Setiyorini; Eri Haryanto (Universitas Janabadra, 2022)
Information systems are a combination of work procedures, information, people, and information technology that are organized to achieve goals within an organization. Criteria for a good information system, among others, are flexible, effective and efficient. To improve the performance of the BAAK (Academic and Student Administration Unit) at Janabadra University, a tool is needed in the form of an information system to handle administrative submissions which so far are still done manually and students have to come directly to campus. This study applies the agile development method with the Scrum framework in designing a website-based academic administrative information system. The Scrum method approach was chosen because it provides a framework for continuous feedback and exposure to ensure that the resulting system quality is as good as possible. The resulting system is able to handle the process of submitting academic administration online, namely submitting college leave, submitting active returns, submitting class program transfers, submitting study programs, submitting resignations as students, submitting certificates and submitting readmissions. This system is expected to improve BAAK services to students and reduce physical contact because students do not need to come directly to campus. In addition, this student academic administration service system can reduce the risk of losing academic submission documents and the advantage of this system is that it can overcome the obstacles of physically signing documents with a QR Code based digital signature.